Correlation of Work Period and Age with the Compliance with the Use of Ear Protection Equipment on Production Workers in anEast Java Animal Feed Industry - Zikri Fathur Rahman; Fatma Nuriyanti Mochtar; Yustinus Denny Ardyanto (The Indonesian Journal of Occupational Safety and Health, 2021)
ABSTRACTIntroduction: Ear protection equipment is indispensable for workers exposed to noise exceeding the threshold value. Introduction: Many studies have shown that the level of labor compliance with the use of ear protection equipment is influenced by the length of work and age of the workers concerned. However, many studies also show different conditions with the results of these studies. For this reason, this study was conducted to determine how the influence of the work period and age of workers on the compliance with the use of ear protection equipment at PT X animal feed industry. Methods: The method used was observational with a cross-sectional approach. The number of population selected from animal feed production workers was 30 workers. The sample was obtained using a simple random sampling calculation of 28 workers. The analysis was done using contingency coefficient statistical tests. Results: The number of workers in the study area whose tenure <12 years is 50% and whose age <37 years is was also 50%. By using the contingency coefficient, it is known that there are 39.3% and 35.7% of 64.3% of workers who were not compliant with the useof ear protection equipment, each having a work period of <12 years and age <37 years respectively. It is also known that work period and age of workers have a Sig (0.115)> α (0.05) and Sig (0.430)> α (0.05) accordingly, which means there is no relationship between work period and the age of the workers with the compliance with the use of ear protection equipment. Conclusion: The reasons of the non-compliance of workers with the use of ear protection equipment are they feel uncomfortable, they have a lack of supervision, as well as they have a lack of motivation work.age, animal feed, compliance, ear protection equipment, years of service